PENGEMBANGAN LKS IPA BERBASIS KEARIFAN LOKAL KOPI PADA POKOK BAHASAN USAHA DAN ENERGI DI SMP - Rosita Sari; Alex Harijanto; Sri Wahyuni (FKIP Universitas Jember, 2018)
AbstractThe purpose research and development of students worksheets science based onlocal wisdom of coffee on the subject effort and energy were described validity of product,described critical thinking skill of students and described students response. Thisworksheets arranged with indicators of critical thinking were interpretation, analysis,inference, evaluation, explanation, and self regulation. The design of this research anddevelopment by Sugiyono that was (1) potential and problem, (2) data collection, (3) theproduct design, (4) validation design, (5) revision design, (6) testing products, and (7)revision products. The techniques of data collection were validity, test, questionnaire,and documentation. The result showed that (1) the students worksheets science based onlocal wisdom of coffee was very valid and value of validation 86,43 % it can be usedwithout revision; (2) the students worksheets science based on local wisdom of coffee waseffective to increase critical thinking skill of students and value indicators of criticalthinking skill 72,99 % with good predicate, and N-gain value 0,47 with medium category;and (3) the students worksheets science based on local wisdom of coffee was verypractically to students and the value of students response 85,98% with very goodcategory.Key word: local wisdom, validity, critical thinking, students response